Design in an iconic landscape: residential architecture policy and practice in Dartmoor National Park (1997-2017) - Tatum, Kirsten L. (2019)
In England’s national parks, architecture represents a contested part of landscape planning, inseparable from park conservation ideologies and policies. Notions of appropriate and contextual architecture are inherently linked to landscape values, but there is little comparative research into the significance of these values in shaping approaches to the design and planning of new architecture. In national parks landscape values are often in tension: power struggles over the preservation or conservation of natural and cultural heritage divide opinion and communities, and new developments can be celebrated as enhancing the landscape or decried for destroying it. Meanwhile, landscape conservation aims must be reconciled with the interests and views of local stakeholders, including accommodating demands for new housing.